Civilized truths, hateful lies? Incivility and hate speech in false information – evidence from fact-checked statements in the US. Issue 11 (18th August 2022) - Hameleers, Michael; van der Meer, Toni; Vliegenthart, Rens
ABSTRACT: Digital information settings may not only offer an opportunity structure for democratic deliberation, but also facilitate the occurrence of negative phenomena – such as incivility, hate speech and false information. Even though extant literature has provided theoretical arguments for a discursive affinity between false or deceptive information and uncivil speech, we lack empirical evidence on whether and how false information and incivility converge. Against this backdrop, we rely on an extensive content analysis of fact-checked statements in the US ( N = 894) to assess to what extent and how different forms of incivility are present in different degrees of false information. Our main findings illustrate that partisan attacks, negativity, and hate speech are most likely to occur in false information that deviates furthest from reality. These findings help us to dissect different degrees of untruthfulness based on their content features: Disinformation (goal-directed deception) may be distinguished from misinformation (unintentionally misleading content) based on the centrality of hostility, partisan attacks, and hate speech in the former.